Soft facts: Thinking practices and the architecture of reality - Bensusan, Hilan Nissor; Pinedo García, Manuel de (Daimon Revista Internacional de Filosofia, 2013)
It is common to criticize the idea of objectivity by claiming that we cannot make sense of any cognitive contact with the world that is not constituted by the very materials of our thinking, and to conclude that the idea must be abandoned and that the world is ‘well lost’. We resist this conclusion and argue for a notion of objectivity that places its source within the domain of thoughts by proposing a conception of facts, akin to McDowell’s, as thinkable while independent of any act of thinking. However, we do so without any empiricist commitment.